The unsupported and immobilized Titanium Dioxide and Zinc Oxide phatacatalysts for the degradation of Amine, Paraquat and Phenol [electronic resource] - 263758 Noraidura Amin (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2007